Effect of Acute Exposure of Cigarette Smoke on Endometrium Thickness and Number of Ovarian Follicles in Rats - Izdihar Ramadhanty Abiyasa Putri; R Haryanto Aswin; Tri Hartini Yuliawati (Universitas Airlangga, 2021)
Background: Cigarrete smoke has been ascociated with many health-related problems especially in long time use. One of many health problems that are affected is the reproductive system that give negative impact in fertility. However, there are limited studies about this in acute exposure of cigarette smoke. Objective: The aim of this study is to investigate the effect of acute exposure of cigarette smoke on endometrial thickness and number of ovarian follicles in rats. Methods: Thirty adult female rats were randomly divided into 3 groups: P0, P1 and P2. The P1 and P2 groups were exposed to cigarette smoke for 15 days with dose of 2 and 4 cigarettes daily, respectively. Vaginal swab was done twice, before and after the last treatment, to determine the proestrus phase of the animals. Histological slide of uterus and ovarium using Haematoxylin Eosin staining were observed under light microscop. Number of ovarian follicles were measured, and the thickness of endometrium was meassured using CellSens software version 2.3 (Olympus Life Science). Statistical analysis of data was performed using MANOVA in SPSS software version 23 for Windows. Results: There were no significant differences in both endometrial thickness and number of ovarian follicles between 3 groups (p>0.05). However, we found that there were a downward trend of some variables (endometrial thickness, number of primary follicles, de Graff follicles, and corpus luteum) from P0 to P2. Conclusion: We concluded that acute exposure of cigarette smoke not yet influenced the female reproductive organ, based on histological appearance of endemotrium and ovarium.